Random linear network coding based physical layer security for relay‐aided device‐to‐device communication. Issue 7 (1st April 2020) - Khan, Amjad Saeed; Chatzigeorgiou, Ioannis; Zheng, Gan; Basutli, Bokamoso; Chuma, Joseph M.; Lambotharan, Sangarapillai
Abstract : The authors investigate physical layer security design, which employs a random linear network coding with opportunistic relaying and jamming to exploit the secrecy benefit of both source and relay transmissions. The proposed scheme requires the source to transmit artificial noise along with a confidential message. Moreover, in order to further improve the dynamical behaviour of the network against an eavesdropping attack, aggregated power controlled transmissions with optimal power allocation strategy is considered. The network security is accurately characterised by the probability that the eavesdropper will manage to intercept a sufficient number of coded packets to partially or fully recover the confidential message.